JENIS TUMBUHAN OBAT TRADISIONAL DARI MASYARAKAT DAYAK KENYAH UMA BAHA DI KECAMATAN KELAY KABUPATEN BERAU - Lonita Lonita; Medi Hendra; Nova Hariani (Jurnal Pro-Life, 2019)
medicine in the Dayak Kenyah Uma Baha tribe. The method that used in this research is an exploratory survey with the PRA (Participatory Rural Appraisal). The result shows that there are 70 medicine plants species which grouped into 39 families and obtained from 45 respondents. The part of the plant that usually used by the Dayak Kenyah Uma Baha tribe is root, tuber/rhizome, stem, tree bark, sap, leaves, flowers, fruit, and seed. The most commonly used are leaves (54%) and the least used part is a flower (1%). The process traditional medicinal plants carried out by the Dayak Kenyah Uma Baha tribe is to be boiled, pounded, grated, squeezed, brewed, burned and directly used. The most commonly used method is boiled (35%) and the least used method is burning (1%). The utilization of habitus based medicinal plants used by the Dayak Kenyah Uma Baha tribe is herbaceous habitus (39%) and the least used is epiphytic habitus (1%). Keyword: Dayak Kenyah Uma Baha tribe, traditional medicinal plants, medicinal plants species